Moderating effect of government regulations on the determinants of customer loyalty for cellular service providers in Pakistan - Tariq, Beenish; Najam, Hammad; Maat, Nik Kamariah Nik; Han, Heesup (The journal of contemporary issues in business and government, 2020)
Customer loyalty has become essential for the survival/success of cellular service providers with the saturation and maturity of the cellular service sector of Pakistan. This research focuses on the direct determinants of customer loyalty of the prepaid segment in the cellular service sector of Pakistan. This study investigates the direct influence of perceived service quality, sales promotion and perceived corporate social responsibility on customer loyalty, and explores the role of government regulations as a moderator that affects the relationship between customer loyalty and its determinants (perceived service quality, sales promotions, perceived corporate social responsibility). This study also provides some valuable insights for the cellular service sector of Pakistan.